Disposable 3D-printed flow cell biosensor for pathogenic Escherichia coli bacteria detection - Redzuan, Muhammad Fadzlisyam; Ismadi, Irfan Danial; Mohamad Azmi, Muhammad Fakhrullah; Ibrahim, Izzah Afifah; Mohd Ghazali, Mohd Ifwat; Mohamed, Nurul Azmawati; Tamchek, Nizam; Abdullah, Shahino Mah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This research seeks to develop an innovative 3D-printed biosensor for the rapid and accurate detection of Escherichia coli (E. coli) bacteria in water samples. The proposed biosensor will incorporate a flow cell design, which allows continuous monitoring and efficient detection of E. coli in real-time. The sensor will be fabricated using conductive polymer-based materials integrated with specific biological recognition elements to ensure high sensitivity and specificity. The 3D printing technology will be utilized to create a precise and reproducible flow cell structure, optimizing the sensor's functionality and scalability. The research will proceed through several key phases: designing and simulating the flow cell structure, selecting and functionalizing the sensing materials, fabricating the biosensor using 3D printing techniques, and conducting extensive testing with water samples containing various concentrations of E. coli. This research will establish a foundation for future advancements in portable and effective biosensing devices for early detection of bacterial contamination.